Compassionate Curiosity: Mitigating the Effects of Bias Through Motivational Interviewing - Paul J. Hershberger; Dean A. Bricker; Angie Castle; Timothy N. Crawford; Stacy R. Flowers; Alexandria L. Goff; Katharine Conway (Mary Ann Liebert, 2024)
There is strong evidence that the implicit biases of health care professionals affect the treatment of patients, and that minority and other marginalized patients are disproportionately harmed. Assumptions made about patient knowledge or lack thereof function as judgments that are prone to bias, which then affect the education and advice imposed upon patients. We review how the motivational interviewing (MI) approach to patient engagement includes components of evidence-based bias-mitigating strategies, such as understanding circumstances from the patient?s point of view, and therefore we propose that the MI approach can reduce the impact of bias in patient care.